ERUPTIVE HISTORY OF KARYMSKY VOLCANO, KAMCHATKA, USSR, BASED ON TEPHRA STRATIGRAPHY AND 14C DATING - Braitseva O.A.; Melekestsev I.V. (My University, 1991)
Eruptions of the active Karymsky stratovolcano began about 5300 (6100 C-14) B.P. from within a pre-existing caldera which formed 7700 C-14 B.P. As indicated by 32 C-14 determinations on buried soils and charcoal, the volcano has gone through two major cycles of activity, separated by a 2300 year period of repose. The first cycle can be divided into two stages (6100-5100 and 4300-2800 B.P.). The earlier stage began with especially intense eruptions of basaltic andesite to dacite. The later stage was characterized by moderate-strength eruptions of andesite. The second cycle, which is characterized by weak to moderate intermittent eruptions of andesite, started 500 B.P. and continues to the present. Eruptive patterns suggest that this cycle may continue for at least another 200 years with an eruptive character similar to that of the recent past.
Keywords: 38.29.23 Стратиграфия кайнозоя; 38.37.25 Вулканология; Карымский